2011
DOI: 10.1037/a0023151
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pathways to adolescent cannabis abuse and dependence: Child maltreatment, emerging personality, and internalizing versus externalizing psychopathology.

Abstract: Child maltreatment is strongly associated with adolescent psychopathology and substance abuse and dependence (Clark, Thatcher, & Martin, 2010; Ellis & Wolfe, 2009). However, developmental processes unfolding from childhood into adolescence that delineate this trajectory are not well understood. The current study uses path analysis in a structural equation modeling framework to examine multiple mediator models, including ego control, ego resiliency, and internalizing and externalizing symptoms to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
87
2
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 71 publications
17
87
2
6
Order By: Relevance
“…The broad range of risk and resilience factors assessed by the full clinical battery will allow for the effects of multiple domains to be examined in concert when evaluating the influence of alcohol on brain development during the adolescent years. For example, the relationship between externalizing/conduct disorder symptoms and risk for alcohol use has been described for many years (Anderson et al, 2010;Slutske et al, 1998), but the emergence of symptoms over the course of adolescence and the interaction of externalizing symptoms with emerging symptoms from other domains have not been fully examined in such a large sample and with the breadth of assessments in the current study (Hussong et al, 2011;Oshri et al, 2011). Based on previous reports associating these risk domains with drinking during adolescence, the NCANDA sample is well positioned to capture transitions to heavy alcohol consumption during the 4 years of data collection and examine brain changes in relation to use characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…The broad range of risk and resilience factors assessed by the full clinical battery will allow for the effects of multiple domains to be examined in concert when evaluating the influence of alcohol on brain development during the adolescent years. For example, the relationship between externalizing/conduct disorder symptoms and risk for alcohol use has been described for many years (Anderson et al, 2010;Slutske et al, 1998), but the emergence of symptoms over the course of adolescence and the interaction of externalizing symptoms with emerging symptoms from other domains have not been fully examined in such a large sample and with the breadth of assessments in the current study (Hussong et al, 2011;Oshri et al, 2011). Based on previous reports associating these risk domains with drinking during adolescence, the NCANDA sample is well positioned to capture transitions to heavy alcohol consumption during the 4 years of data collection and examine brain changes in relation to use characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, Swift et al (2008) found that persistent anxiety and depression were also associated with an increased risk of later cannabis problems and dependence. Another longitudinal study of children and adolescents demonstrated support for a particular developmental pathway to adolescent cannabis use disorders; whereby severity of early childhood maltreatment potentiated less adaptive childhood personality functioning, followed by externalizing problems in preadolescence, and ultimately, adolescent cannabis abuse and dependence symptoms (Oshri, Rogosch, Burnette, & Cicchetti, 2011). Interestingly, a developmental pathway from child maltreatment to adolescent cannabis use disorder symptoms via personality and preadolescent internalizing problems was not supported (Oshri et al, 2011 (Agrawal et al, 2011;Verweij et al, 2012).…”
Section: Etiology Of Cannabis Use Disordersmentioning
confidence: 99%
“…These considerable differences between frequent cannabis users and the general population were responsible for the attenuation of most of the mental health differences between the user groups and the general population sample, most prominently regarding the high prevalence of internalizing disorders in dependent frequent users. Based on the assumed chronology, one may suggest that childhood adversity is partly responsible for the co-occurrence of cannabis dependence and mental disorders later in life [29]. However, compared to the general population, nondependent users also had more childhood adversity without a higher risk of internalizing disorders.…”
Section: Childhood Adversity and Substance Usementioning
confidence: 99%
“…This is also true for childhood adversities [27,28]. In particular, it has been suggested that the development of cannabis abuse and dependence symptoms are influenced by childhood maltreatment both directly and through the development of externalizing (but not internalizing) disorders [29]. Although these factors do not negate mental health differences, they should be considered as alternative explanatory factors for mental health differences between these groups.…”
Section: Introductionmentioning
confidence: 99%